CMOS X-rays microdetector based on scintillating light guides - Rocha, J. G. (2002)
This paper describes a pixel imaging array consisting in 400 um x 400 um photodiodes fabricated in CMOS technology. Above the photodiodes, an array of scintillating CsI:Tl crystals are placed. The scintillating crystals are encapsulated in aluminum walls forming a light path to guide the produced visible light into the photodiodes. So, the x-ray energy is first converted into visible light which is then detected by the photodiode at the end of each light guide. The scintillator is 800 um thick, absorbing almost all of 20 keV x-ray photons. Usually, the spatial resolution of the scintillating x-rays detectors is identical to the scintillator thickness. By using the light guides, the scintillator thickness can be increased, without decreasing the spatial resolution. The increase of the scintillator thickness is desirable in order to increase the x-rays absorption efficiency. Tests carried out on the system show very promising results near 20 keV.